2017
DOI: 10.1080/00313831.2017.1306800
|View full text |Cite
|
Sign up to set email alerts
|

International Week in a Norwegian School. A Qualitative Study of the Participant Perspective

Abstract: This article explores an international week in a Norwegian primary school from the perspective of the different participants in the arrangement. International week is typically organized in connection with the United Nation's day and is to contribute to the school's aim of inclusion and social justice. Whereas the research literature has been critical towards such weeks, using terms such as 'exotification' and 'hall-way multiculturalism', there has been scarce research on international weeks from the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
9
Order By: Relevance
“…The school aims at developing pedagogies for culturally and linguistically diverse classrooms, through efforts such as their annual international week. In another publication, we reported on the international week more in general (Dewilde et al 2017). Here, we concentrate on the two-hour-long multicultural festival organised by the parent board in a sports hall connected to the school at the end of the international week (see also Basha and Kjørven 2018), and more specifically on the Kurdish stall.…”
Section: The Study's Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The school aims at developing pedagogies for culturally and linguistically diverse classrooms, through efforts such as their annual international week. In another publication, we reported on the international week more in general (Dewilde et al 2017). Here, we concentrate on the two-hour-long multicultural festival organised by the parent board in a sports hall connected to the school at the end of the international week (see also Basha and Kjørven 2018), and more specifically on the Kurdish stall.…”
Section: The Study's Design and Methodsmentioning
confidence: 99%
“…However, the study delved more deeply into the perspectives of the school leadership, the teachers, the students, and the parents, and the authors concluded that the international week was experienced as 'a powerful social space where constructions of new identities take place' (Author 1, Author 2, Colleague and Author 3, xxxx). Being well aware of the criticism from the research field, the school's principal remained steadfast, claiming 'the international week is a symptom of what the school is all about' (Dewilde, Kjørven, Skaret, and Skrefsrud 2017), as it serves to establish 'a common understanding of the school as a multicultural school. Students get to know each other across classes, groups, and language.…”
Section: Prior Research On the Subject Mattermentioning
confidence: 99%
“…This assumption has also resulted in practices of multicultural education that celebrate cultural differences at a school through isolated events, such as Multicultural Day, International Week, and International Understanding Day (Dewilde, Kjørven, Skaret, & Skrefsrud, 2018). Such events are often characterized as a festivalization of culture (Øzerk, 2008), corresponding with Troyna and Carrington's (2012) well‐known description of the three S's of multicultural education: saris, samosas, and steel bands; that is to say, clothing, food, and music.…”
Section: Intercultural Understanding: a Conventional Approach And Itsmentioning
confidence: 99%
“…Tiltaka som er referert til i denne artikkelen, kan kanskje virke enkle og lite banebrytande, men det er likevel starten på noko nytt. Ifølge Dewilde et al (2018) kan dei små steg knytt til konkrete tiltak også endre hierarkiet og styrkeforholdet mellom aktørane. Difor er refleksjonen som føregjekk gjennom dei semistrukturerte intervjua, men ikkje minst i fokusgruppe-samtalene, etter mitt syn svaert viktig.…”
Section: Drøftingunclassified